RELEVANSI NILAI-NILAI PANCASILA DALAM KEHIDUPAN MAHASISWA DI ERA DIGITAL - Clarissa Florencia; Raja Oloan Tumanggor; Angelica Noverina; Shafa Zalikha Putri; Karelina Primavitri; Asmaul Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of information and communication technology in the digital era has significantly transformed how students interact, communicate, and access information. On one hand, the digital era provides vast opportunities for students to innovate and contribute to national development; on the other hand, it presents challenges such as misinformation, declining privacy, and weakened social and national values. As digital natives, students are required to use technology ethically, critically, and responsibly. In this context, Pancasila values remain highly relevant as moral and ethical guidelines in navigating globalization and digital culture. This article aims to explain the relevance of Pancasila values in students’ lives in the digital era, emphasizing its role in fostering ethical and nation-oriented digital literacy. This study employs a literature review method, analyzing academic sources such as journals, books, and conference proceedings published between 2015 and 2025. The findings indicate that the internalization of Pancasila values through higher education and digital literacy plays a crucial role in shaping students’ integrity, adaptability, and national responsibility amid globalization.